Analysis Of The Effect Of Excitation Current On The Synchronology Generator On Loading At Plta Renun PT PLN (Persero) UPDK Pandan - David Simanullang; Siti Anisah; Hamdani (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This study will discuss the effect of the excitation current of the PLTA RENUN synchronous generator on each load change to maintain the nominal output voltage of the generator with a variable transmission voltage of 150 kV. The analysis data is obtained from the Daily Operation Report of the RENUN HEPP in accordance with changes in the generator load or changes in the value of the transmission voltage to determine its effect on changes in the AVR excitation current. The daily data obtained is then compared with the initial setting or AVR characteristics during the Commissioning Test, the resulting deviation will be used as input for the Pandan UPDK Engineering in carrying out the next corrective action. Thus the reliability of the PLTA RENUN in serving P2B to maintain the stability of the 150 kV Sumbagut transmission system is maintained.